2021
DOI: 10.3390/infrastructures6020025
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Gerber Saddles in RC Bridges: Analyses and Applications (Musmeci Bridge, Italy)

Abstract: Guaranteeing adequate safety levels in critical infrastructures such as bridges is essential to modern societies and their vital services. Bridges with reinforced concrete structures are subject to deterioration, especially due to corrosion effects. Gerber saddles are among the key components of bridges which are especially exposed to environmental actions due to their position and reduced possibility of inspection. In this paper, a framework for the durability analysis of these components is proposed, conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Only the analysis and design of B-regions can proceed on a sectional basis for which plane sections remain plane, whereas the analysis and design of D-regions must proceed on a regional basis. Some of the many references are [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Statement Of the Issue Being Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the analysis and design of B-regions can proceed on a sectional basis for which plane sections remain plane, whereas the analysis and design of D-regions must proceed on a regional basis. Some of the many references are [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Statement Of the Issue Being Addressedmentioning
confidence: 99%
“…This point merely reviews some well-known generalities about the cracking behavior of a simply supported RC beam with web-reinforcement, under uniform loading [ 15 , 18 , 19 , 26 , 28 , 37 , 40 , 43 ]. The review includes extensions to the doubly fixed RC beam.…”
Section: Statement Of the Issue Being Addressedmentioning
confidence: 99%
“…This is even clearer after the Morandi bridge collapse that killed 43 people in August 2018 [2,3] and forced motorway traffic to take an urban detour with consequent jams. Therefore, aging and degradation effects must be seriously considered in order to evaluate the residual life span of each bridge structure [4].…”
Section: Introductionmentioning
confidence: 99%
“…The rapidly growing industrialization, urbanization and population significantly increased the demands and developments in the construction industry [ 4 ]. Concrete has gained a vital role in the construction industry because of its low price, the convenience of its raw materials, high compressive strength and durability [ 5 ]. The properties of concrete are significantly influenced by the characteristics of aggregates which typically occupy a total of 65–80% of its volume [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To examine the durability characteristics of plastic concrete, durability tests were also carried out [ 35 , 36 ], which reported that concrete with plastic aggregate is acceptable and has better results with respect to control concrete. It was revealed that the plastic concrete seems to be satisfactory for utilization in aquatic structures as the durability characteristics are of major concern in marine structures [ 5 ], and compared with control concrete, the plastic concrete has shown higher resistivity against sulfate and chloride attack [ 8 , 37 ]. Additionally, from previous studies, it was reported that the workability of concrete containing plastic aggregates increases with respect to control concrete, owing to the zero water absorption capacity of plastic aggregate [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%